KEMATANGAN EMOSI DAN PENYESUAIAN PERKAWINAN PADA USIA PERKAWINAN 5 TAHUN PERTAMA - Permatasari, Juwita; Kumala, Anisia (Jurnal Ilmiah Penelitian Psikologi, 2021)
Marital adjustment for couples in the first five years of marriage is a important thing in their marriage. Marital adjustment is an important process in a household ark in determining the integrity of the household. In the process of marital adjustment, emotional maturity is needed for each individual. The purpose of this study is to determine the relationship between emotional maturity and marital adjustment in the first 5 years of marriage. Respondents in this study amounted to 214 married couples consisting of 107 husbands and 107 wives. In selecting the subject, the researcher used the nonprobability sampling method which consisted of the Dyadic Adjustment Scale (DAS) compiled by Spanier as many as 13 items with a Cronbach alpha value of 0.657. The Emotional Maturity Scale (EMS) compiled by Yashwir Singh & Mahesh Bhargave consists of 32 items with a Cronbach alpha value of 0.839. The results of the analysis show that there is a significant positive correlation between emotional maturity and marital adjustment in the first five years of marriage. The implications of these results will be discussed later.